Mechanical Properties of Spun Castings of Multicomponent Bronze Depending on the Casting Conditions; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Korchmit A. V. Anton Viktorovich (Material Engineering and Technologies, 2015)
Title screen